A Grounded Theory of Veterans' Experiences of Addiction-as-Occupation. Issue 1 (2nd January 2016) - Wasmuth, Sally; Brandon-Friedman, Richard A.; Olesek, Kyle
Abstract : This study examined how addiction emerges as an occupation in the lives of veterans. Its purpose was to facilitate better knowledge of how addiction is experienced as an occupation by this population, with the goal of destigmatizing addiction and paving the way for innovative ways to help people with addictions to build new occupational lives. Fifty-eight veterans diagnosed with a substance use disorder were recruited from a VA residential treatment center, of which 35 transcripts of the Indiana Psychiatric Illness Interview—a broad interview inquiring about participants' life experiences—were randomly selected for grounded theory analysis following a 4-step coding procedure as outlined by Charmaz. Data revealed a five step occupational process: Being Initiated; Increasing Engagement; Establishing an Identity; Experiencing Discord and Defeat; and Finding Other Occupations. Addiction is discussed as a behavioral pattern, and the authors discuss how the use of new occupations may provide individuals with new patterns of organization, social interconnection, and identity development needed to sustain a move away from occupations of addiction.